TERMS «BILINGUALISM» AND «DIGLOSSIA» IN SOCIOLINGUISTICS - Матвеєва, Наталя (Linguistic Bulletin (Movoznavchyi Visnyk), 2019)
Much research has been devoted to the phenomena of bilingualism and diglossia, unfortunately they still remain a contradicting point. This article describes different ideas of the Ukrainian and the foreign scientists about these concepts. The purpose of the present investigation is to outline different definitions of the concepts «bilingualism» and «diglossia» and formulate their distinctive features. Presented in the article is the analysis of the different ideas of soviet and foreign linguists about the concepts of bilingualism and diglossia. Results. Bilingualism is considered by many authors as a phenomenon, when both languages are equal for speakers and perform the same functions. The term diglossia is more contradictory. Although this phenomenon has been studied by western researchers there is no definite opinion about this term.The differences in views on this concept lie in the fact that some scientists interpret it as the usage of different languages, while others say that only different variants of language are used. But the main feature of diglossia, which differentiates it from bilingualism, is a conscious attitude to each of languages and their clear differentiation as prestigious or non-prestigious, formal or informal. In contrast the bilingual situation means that the speakers equally use two languages in different communicative situations. Conclusions. From all this investigation we can make a conclusion that the term bilingualism is typically used to describe two languages, used by individual, while diglossia is the situation when different languages may be used for different purposes; it is the result of the functional separation, conscious choice of particular languge in order to achieve communicative success. That is why bilingualism and diglossia can exist together and separately in different language groups